Evolutionary relationships and systematics of Atoposauridae (Crocodylomorpha: Neosuchia): implications for the rise of Eusuchia. (13th July 2016) - Tennant, Jonathan P.; Mannion, Philip D.; Upchurch, Paul
Abstract : Atoposaurids are a group of small‐bodied, extinct crocodyliforms, regarded as an important component of Jurassic and Cretaceous Laurasian semi‐aquatic ecosystems. Despite the group being known for over 150 years, the taxonomic composition of Atoposauridae and its position within Crocodyliformes are unresolved. Uncertainty revolves around their placement within Neosuchia, in which they have been found to occupy a range of positions from the most basal neosuchian clade to more crownward eusuchians. This problem stems from a lack of adequate taxonomic treatment of specimens assigned to Atoposauridae, and key taxa such as Theriosuchus have become taxonomic 'waste baskets'. Here, we incorporate all putative atoposaurid species into a new phylogenetic data matrix comprising 24 taxa scored for 329 characters. Many of our characters are heavily revised or novel to this study, and several ingroup taxa have never previously been included in a phylogenetic analysis. Parsimony and Bayesian approaches both recover Atoposauridae as a basal clade within Neosuchia, more stemward than coelognathosuchians, bernissartiids, and paralligatorids. Atoposauridae is a much more exclusive clade than previously recognized, comprising just three genera ( Alligatorellus, Alligatorium, and Atoposaurus ) that were restricted to the Late Jurassic of western Europe, and went extinct at the Jurassic/Cretaceous boundary. A putative Gondwanan atoposaurid ( Brillanceausuchus ) is recovered as a paralligatorid. Our results exclude both Montsecosuchus and Theriosuchus from Atoposauridae. Theriosuchus is polyphyletic, forming two groupings of advanced neosuchians. Theriosuchus (restricted to Theriosuchus pusillus, Theriosuchus guimarotae, and Theriosuchus grandinaris ) spanned the Middle Jurassic to early Late Cretaceous, and is known from Eurasia and North Africa. Two Cretaceous species previously assigned to Theriosuchus (' Theriosuchus ' ibericus and ' Theriosuchus ' sympiestodon ) are shown to be nested within Paralligatoridae, and we assign them to the new genus Sabresuchus . The revised phylogenetic placement of Theriosuchus has several implications for our understanding of eusuchian evolution. Firstly, the presence of fully pterygoidean choanae, previously regarded as a defining characteristic of Eusuchia, is not found in some basal members of Eusuchia. However, eusuchians can be distinguished from Theriosuchus and other basal neosuchians in that their choanae are posteriorly positioned, with an anterior margin medial to the posterior edge of the suborbital fenestra. This feature distinguishes eusuchians from Theriosuchus and more basal neosuchians. Secondly, our refined understanding of Theriosuchus implies that this taxon possessed only amphicoelous presacral vertebrae, and therefore fully developed vertebral procoely is likely to have evolved only once in Crocodylomorpha, on the lineage leading to Eusuchia. These and other findings presented herein will provide an important framework for understanding the neosuchian–eusuchian transition.